Handbook of economic field experiments - Banerjee, Abhijit V.; Duflo, Esther 1972 (Amsterdam, Netherlands North-Holland, an imprint of Elsevier, 2017)
"Handbook of Field Experiments provides tactics on how to conduct experimental research, also presenting a comprehensive catalog on new results from research and areas that remain to be explored. This updated addition to the series includes an entire chapters on field experiments, the politics and practice of social experiments, the methodology and practice of RCTs, and the econometrics of randomized experiments. These topics apply to a wide variety of fields, from politics, to education, and firm productivity, providing readers with a resource that sheds light on timely issues, such as robustness and external validity."--Provided by publisher.
Volume 1. An introduction to the "handbook of field experiments" A.V. Banerjee, E. Duflo -- Section I. Some historical background. The politics and practice of social experiments : seeds of a revolution J.M. Gueron -- Section II. Methodology and practice of RCTs. The economics of randomized experiments / S. Athey, G.W. Imbens -- Decision theoretic approaches to experiment design and external validity A.V. Banerjee, S. Chassang, E. Snowberg -- The practicalities of running randomized evaluations : partnerships, measurement, ethics, and transparency R. Glennerster -- The psychology of construal in the design of field experiments E.L. Paluck, E. Shafir -- Section III. Understanding preferences and preference change. Field experiments in markets O. Al-Ubaydli, J.A. List -- Field experiments in discrimination M. Bertrand, E. Duflo -- Field experiments on voter mobilization : an overview of a burgeoning literature A.S. Gerber, D.P. Green -- Lab in the field : measuring preferences in the wild U. Gneezy, A. Imas -- Field experiments in marketing D. Simester.
Includes bibliographical references and index.
Keywords: Economics -- Experiments -- Methodology; Economics -- Research; Experimental design